Legal protection of victims under criminal law in the Republic of Macedonia - Bačanović Oliver (Temida)
The author tried to outline the status of crime victims in Macedonian criminal and juvenile legislation by analyzing three legal texts referring to legal protection of victims under criminal law in the Republic of Macedonia (the Criminal Code, the Law on Criminal Procedure Act and the Law on Juvenile Justice). The basic questions which have been analyzed from the criminal substantial aspect include: the rights and interests of the victims as a consistent part of contemporary criminal policy and Criminal Code reforms, the elements of diversion model based on concept of restorative justice in criminal legislation and victimology aspects of some significant novelties in the special part of criminal law. In this article two dimensions dealing with a change of status of damaged person in criminal procedure of the Republic of Macedonia have been analyzed, while taking into consideration new trends and comparative experiences in this field. One dimension is the role of the damaged person and incorporation of elements of restorative justice in the criminal procedure, while the other dimension includes help and support of the victims and prevention of their secondary victimization. While analyzing suitable provisions of the Law on Juvenile Justice, the author focuses on its solutions that deserve more attention because of its innovations. The consequent realization of the concept on which this law is based on, and in which the victim, at the same time, has a significant role is another confirmation of the rule that the changes of juvenile legislation creates good basis for future reforms of criminal legislation regarding the adult offenders.